EFEKTIFITAS PEMBELAJARAN MATEMATIKA MODEL KOOPERATIF TEAMS GAMES TOURNAMENT (TGT) KELAS VII SMP ISLAM KOTA PEKALONGAN TAHUN 2009/2010 MATERI SEGIEMPAT - Muchamad Subali Noto (LPPM Universitas Pekalongan, 2011)
This is an experimental research, and the research question is that will the Teams Games Tournament (TGT) Cooperative Model in learning quadrilateral at SMP Islam Pekalongan be effective?, Field study is chosen to find out the populations of SMP Islam Pekalongan that consists of 8 classes, using the random technique sampling and determined that class VII(8) as the control class and class VII(3) as the experiment class. The variables; students’ activeness is as the independent variable and process skill is as the dependent variable. The data is derived from the learning test achievement and experiment sheets. The research method is descriptive, the analysis of the t test sample and regression. The hypothesis tests using simultaneous study too find out the students’ achievement in classical or individual, and the influence of students’ activeness and the skill process to the learning achievement. The results of the research are that the learning is considered to be effective, signed by 3 indicators, they are; (1) the students’ achievement is up to the classical criteria that is 69,33 more than KKM 65, and the individual achievement is 75%, (2) the students’ activeness and skill process have positive influences to the students’ achievement, the activeness has an influence to the learning achievement to 80,30%, the influence of the skill process is 69,00%, and both of them are 81,50%, (3) the experiment class’s achievement is 69,33 better than the control class in average 61,60%.Key words: Learning effectiveness, TGT, Quadrilateral